1999
DOI: 10.2307/177021
|View full text |Cite
|
Sign up to set email alerts
|

The Fern Understory as an Ecological Filter: Emergence and Establishment of Canopy-Tree Seedlings

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology. Abstract.We investigated the role of the fern understory as an ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
147
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 104 publications
(157 citation statements)
references
References 29 publications
5
147
0
5
Order By: Relevance
“…However, many field surveys contradict these expectations when they report a similar performance among seedlings of different oak species along environmental gradients (e.g. Ashton and Larson 1996;Long and Jones 1996;George and Bazzaz 1999, and for Mediterranean oaks (Bacilieri et al 1993;Lookingbill and Zavala 2000). Our experimental study and modelling approach show that pre-dispersal predation may be a key process to explain inter-specific differences in the recruitment of co-occurring oaks.…”
Section: Discussionmentioning
confidence: 66%
“…However, many field surveys contradict these expectations when they report a similar performance among seedlings of different oak species along environmental gradients (e.g. Ashton and Larson 1996;Long and Jones 1996;George and Bazzaz 1999, and for Mediterranean oaks (Bacilieri et al 1993;Lookingbill and Zavala 2000). Our experimental study and modelling approach show that pre-dispersal predation may be a key process to explain inter-specific differences in the recruitment of co-occurring oaks.…”
Section: Discussionmentioning
confidence: 66%
“…Despite the potential for understorey vegetation to act as a major Wlter to recruitment (George and Bazzaz 1999;Royo and Carson 2006), few experiments have tested its multiple eVects on tree seedling establishment through resource and consumer-mediated interactions (Royo and Carson 2008). We found that bamboo presence determined spatial patterns of seedling survival through the Wrst post-emergence summer in a closed-canopy Patagonian forest.…”
Section: Discussionmentioning
confidence: 86%
“…As a result, newly emerged seedlings face a variety of hazards, which operate as ecological Wlters to establishment (Harper 1977;George and Bazzaz 1999), and may ultimately inXuence plant community structure (Silvertown 2004). Vegetation cover plays a major role in shaping the nature of recruitment microsites, by modifying microhabitat conditions and the balance of positive (facilitation) and negative (competition, predation) interactions for emerging seedlings (McAuliVe 1986;Gill and Marks 1991;Callaway and Walker 1997;Holmgren et al 1997;Rousset and Lepart 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations